Successful treatment of a CLL associated IgM hyper-viscosity syndrome: A rare case - Toufic Tannous; Gil Hevroni; Raiyan Islam; Georgios Pongas (Leukemia Research Reports)
In the context of chronic lymphocytic leukemia (CLL), Hyperviscosity Syndrome (HVS) typically arises from hyperleukocytosis, although it infrequently stems from IgM hyperparaproteinemia. We present a distinctive case of HVS induced by IgM hyperparaproteinemia in a patient experiencing relapsed CLL, marked by bulky disease and cytopenias upon progression. The patient exhibited new symptoms, including headache, dizziness, and confusion. Laboratory analysis revealed an elevated total protein level, and serum electrophoresis identified an elevated M spike at 4 g/dL with IgM on immunofixation. Suspecting HVS, prompt plasmapheresis was initiated, resulting in symptom resolution within two days.A comprehensive literature review suggests that CLL patients with an elevated IgM level often face a poor prognosis, though HVS symptoms are not commonly observed. Our case underscores the significance of swiftly identifying HVS when IgM hyperparaproteinemia is detected in CLL patients. Notably, our patient not only achieved successful treatment for the acute presentation but also initiated second-line therapy for relapsed disease. In conclusion, effective management and stabilization of CLL patients with IgM-associated HVS are attainable, emphasizing the crucial role of prompt recognition.